The lovelocks as element of linguistic landscape (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article is devoted to the sociocultural practice of so called lovelocks. This topic has been explored through the perspective of linguistic landscape. The exploration has been conducted on the material of a Uzhhorod bridge (75 lovelocks). We described lingual and stylistic peculiarities of the lovelock texts.
Keywords: sociolinguistics; linguistic landscape; multilingualism; globalization; lovelocks